Regulation of the Minister of Home Affairs Number 77 of 2020: Between Normative Regulation and Mandatory Obligations in Regional Financial Governance - Mohamad Djasuli; Siti Yunia Amalia; Dilla Rachma Ayu; Firdaushil Hasanah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the regulatory characteristics of the Regulation of the Minister of Home Affairs Number 77 of 2020 as a technical guideline for regional financial management, particularly in examining the tension between its normative nature and mandatory provisions, as well as their implications for regional financial governance. The research employs a normative juridical approach, utilizing both statute and conceptual approaches, complemented by a critical analysis of the regulation’s implementation. The findings indicate that, formally, Regulation No. 77 of 2020 is normative in nature as a guideline; however, in practice, it contains numerous mandatory provisions that bind local governments. These mandatory elements have been shown to enhance accountability and transparency through the standardization of procedures, reporting obligations, and strict supervisory mechanisms. On the other hand, the dominance of detailed rules tends to create policy rigidity, increase administrative burdens, and reduce the flexibility and discretion of local governments in adapting policies to local needs. Furthermore, the study identifies a phenomenon of formalistic or ritualistic compliance, which risks producing symbolic accountability without improving the quality of public services. The effectiveness of the regulation’s implementation is also influenced by disparities in human resource capacity, information systems, and regional fiscal capabilities. Therefore, a balance between mandatory approaches and normative flexibility is necessary to ensure that regional financial governance operates effectively, adaptively, and in accordance with the principles of good governance.